STUDI KOMPARATIF KEMAMPUAN MENULIS KARANGAN EKSPOSISI SISWA KELAS XI SMA OLAHRAGA MASMUR DENGAN SMK MASMUR 2 PEKANBARU - Nichy Ariawelsi Ariawelsi; Nursal Hakim; Mangatur Sinaga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aimed to determine the ability of students to write essays exposition class XI  High School Sports with SMK Psalm 2 Psalm Pekanbaru academic year 2014/2015. The sample used in this study as many as 31 people. Each of the first class is divided, in XI High School Sports Psalm12 the number of people. SMK XI Psalm 2 Pekanbaru the number of 19 students. The results of this study are from tests conducted exposition fabricate high school students with vocation  Sports Psalm psalm 2 Pekanbaru. Aspects assessed were explanation are informative are objective, accompanied by concrete evidenc, that is logical, and explain something. Obtained from the calculation of the average value of explaining something. From the calculation, the average vaule of 62,42. The result can be see from the test values obtained fabricatestudents enough of 73,33. And the acquisition value was at 57,10. It can be concluded that the ability of students in class XI High School Sport with SMK Psalm 2 Psalm Pekanbaru. Keywords: writing, essay exposition